The Methodology of Sanad Criticism Employed by Ibn al-Jawzī, al-Suyūṭī, ‎and Ibn Ḥajar in Detecting Mawḍū‘ Hadith: A Comparative Study and Its ‎Relevance in the Digital Era - Dila Kusuma Amanda; Ahmad Syarifudin (Jurnal Ulunnuha, 2026)
The proliferation of fabricated hadiths (maudhu‘) throughout Islamic history, driven by political, sectarian, ‎and ideological motivations, necessitated rigorous methodological frameworks for hadith verification. Ibn ‎al-Jawzī (d. 597 AH) developed one of the most influential yet contested approaches to identifying ‎fabricated narrations through his seminal work al-Maudhu‘āt. While existing studies have examined hadith ‎classification and general principles of hadith criticism, no comprehensive comparative analysis has ‎systematically evaluated the epistemological foundations and methodological distinctions among Ibn al-‎Jawzī, al-Suyūṭī, and Ibn Ḥajar al-ʿAsqalānī within an integrated sanad-matn framework, nor explored their ‎relevance to contemporary digital-era disinformation challenges. This study aims to analyze Ibn al-Jawzī's ‎sanad-criticism methodology for detecting fabricated hadiths in al-Maudhu‘āt, compare it with the ‎methodologies of al-Suyūṭī and Ibn Ḥajar, and evaluate the relevance of these classical approaches to ‎religious information verification in the digital age. This research employs a qualitative approach ‎combining intellectual history analysis, content analysis, and comparative methodology, with al-Maudhu‘āt ‎as the primary data source, supplemented by al-La‘ālī al-Maṣnū‘ah and Lisān al-Mīzān as secondary ‎sources. The findings reveal three epistemologically distinct methodological poles: Ibn al-Jawzī’s ‎eliminative-preventive approach, which prioritizes a single defective transmitter as sufficient grounds for ‎maudhu‘ judgment; al-Suyūṭī’s inclusive-moderate approach, which demands comprehensive cross-chain ‎verification before issuing verdicts; and Ibn Ḥajar’s systematic historico-critical approach, which cross-‎references biographical data and evaluates comment consistency across sources. These three ‎methodologies constitute a layered verification framework applicable to contemporary hadith ‎authentication challenges, particularly for detecting religiously fabricated content on social media and for ‎developing AI-based hadith verification algorithms. This study offers a reconstructed epistemological ‎model of classical hadith verification that bridges pre-modern scholarship and digital-era information ‎literacy, providing methodological foundations for AI-assisted systems for Islamic information ‎authentication.‎